Analisis Ruang Lingkup Anak Berkebutuhan Khusus Pada Sekolah Inklusi - Rafifah Qanita; Sri Wahyuni; Fitratul Mubaraq; Nursyafna Nursyafna; Wismanto Wismanto (LPPM Politeknik Pratama, 2024)
In general, children with special needs are children who have developmental obstacles or abilities above the average for other normal children. Children with special needs (ABK) need special assistance and services so that they can adapt to their environment. The purpose of this article is to describe the characteristics and needs of children with special needs. The method used in this writing is a qualitative method, with a library research approach which makes the main data source come from the latest books, magazines and journals related to the research theme. The results of this research reveal that children with special needs consist of several types of special needs including the blind, the deaf, the physically impaired, to children with special intelligence and special talents (CIBI). Each of them requires special services for each child with special needs. The author also discusses the services needed according to the characteristics of each child with special needs